Dissociative experiences mediate the association between childhood trauma and verbal hallucinations, but not delusional thoughts, in borderline personality disorder - Schroeder, Katrin; Schätzle, Anja; Schäfer, Ingo; Huber, Christian G. (Frontiers in Psychiatry, 2025)
IntroductionAuditory verbal hallucinations (AVH), a disturbance of auditory perception, and delusions, a content-related thought disorder, are common in borderline personality disorder (BPD). However, they are not as thoroughly studied and clinically acknowledged as other symptoms. Associations between childhood trauma, dissociative symptoms, and AVH—as well as delusions—have been reported in schizophrenia but remain understudied in BPD.MethodsWe calculated Pearson’s correlations and tested the mediating effects of dissociative symptoms, assessed with the Dissociative Experiences Scale (DES), on the association between childhood trauma, assessed with the Childhood Trauma Questionnaire (CTQ), and both AVH and delusions. A total of 74 BPD patients were examined using the Psychotic Symptoms Rating Scale (PSYRATS) interview. For the mediation analyses, Preacher and Hayes’ SPSS bootstrap macro was used to estimate the significance of the mediator.ResultsAVH were reported by 10 patients (13.5%) and delusional thoughts by eight patients (10.8%). In the mediator analyses, dissociative experiences significantly mediated the association between childhood trauma and auditory verbal hallucinations, with an unstandardized regression coefficient between CTQ-Total and DES-Total of b = 10.0083; p = 0.0008 and between DES-Total and PSYRATS-AVH of b = 0.0102; p = 0.0009. The relationship between CTQ-Total and the PSYRATS-Delusions Scale was not significantly mediated by DES-Total.DiscussionThe results of the mediation analyses are similar to those shown in schizophrenia, suggesting that the examined symptoms in BPD may underlie similar mechanisms. Further research should examine the benefit of the therapeutic approaches for each of the trauma-associated symptom clusters.